Genetic anticipation of breast cancer among BRCA1/BRCA2 mutation carriers: A retrospective study. Issue 2 (23rd March 2022) - Kedmi, Aviya; Kadouri, Luna; Sagy, Iftach; Hamburger, Tamar; Levin, Gabriel; Zimhony‐Nissim, Noa; Peretz, Tamar
Abstract: Objective: To study the anticipation phenomenon among hereditary breast cancer patients, by evaluating trends in age at diagnosis and phenotype of breast cancer across two successive generation pairs of BRCA1/2 mutation carriers/non‐carriers with breast cancer after reports of an earlier age of diagnosis in successive generations among BRCA1/2 mutation carrier families. Method: A retrospective cohort study. Patient characteristics, pathologic data and survival were compared between mothers and daughters and between carriers and non‐carriers. Results: Overall, 126 patients were found, who formed 67 pairs of mothers and daughters diagnosed with breast cancer and genetically tested for BRCA mutations. Age at diagnosis was significantly younger in the daughter versus mother generation, in both groups of BRCA carriers/non‐carriers. Tumor characteristics were not different between mothers and daughters. Survival analysis revealed a not significant better outcome for the daughter generation versus the mother generation. Conclusions: Breast cancer appeared to be diagnosed at an earlier age in successive generations among BRCA mutation carriers and non‐carriers. The fact that we also observed a downshift at age of diagnosis in non‐carrier pairs emphasizes that other factors (environmental, lifestyle, or social) may influence the age at diagnosis. Abstract : Breast cancer is diagnosed at an earlier age in successive generations among BRCA mutation carriers and non‐carriers.